Faktor-Faktor yang Mempengaruhi Pendapatan Kedai Kopi di Banjarmasin Tengah - Febriana Ramadhani; R Rizali (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This research aims to determine (1) the simultaneous influence of the capital factor and selling price on the income of the Coffee Shop Banjarmasin Tengah District, (2) the partial effect of the capital factor and selling price on the income of the Coffee Shop, Banjarmasin Tengah District, and (3) the most dominant factor influencing the income Coffee shop in Central Banjarmasin District.The research method used was a survey. The data used is quantitative data, namely data in numbers: capital costs, selling price costs, and income tax. The population in this study was 17 coffee shops in the district of Central Banjarmasin. The sampling technique was carried out by simple random as many as 17 selected shops. The data collection technique used in this research is structured interviews. Structured interview. The data collected was analyzed by multiple regression using the SPPS program.The results showed (1) Simultaneously, the working capital and the amount of selling price had a significant effect on the 5% level of coffee shop income in the area of Central Banjarmasin District, Banjarmasin City, because the 5% sign level based on the calculated F value was more significant than the F table, (2) Partially only the amount of the Selling Price and which has a significant effect in the level of 5% on coffee shop income which is spread in the area of Central Banjarmasin District, Banjarmasin City because based on the value of the t count is more significant than the t table, while the Working Capital has no effect because it is at the level of the sign is greater than 5% greater and (3) the selling price has a dominant influence on the income of coffee shops that are spread in the area of Central Banjarmasin District, Banjarmasin City because based on Standardized Coefficients Beta has the most significant number